Development and Field Testing of an HIV Medication Touch Screen Computer Patient Adherence Tool with Telephone-Based, Targeted Adherence Counseling. (November 2013) - McInnes, D. Keith; Hardy, Hélène; Goetz, Matthew B.; Skolnik, Paul R.; Brewster, Amanda L.; Hofmann, Roger H.; Gifford, Allen L.
Background: HIV medication nonadherence is a major problem, yet many providers lack the time and training to carefully ask patients about their adherence. Objective: To design and pilot a technology-assisted intervention, for use in clinical settings, to identify nonadherent patients. Methods: The intervention uses audio computer-assisted self-interview (ACASI) to improve the assessment of adherence and medication-related problems. Patients completed a touch screen computer ACASI which generated graphic clinician and patient reports for discussion during the clinical encounter. Results: 72 patients and 11 providers participated in this study. The patients easily completed the ACASI. Adherence was 63% (3-day) and 47% (30-day). Using the ACASI, 22% of patients identified themselves as nonadherent, when their providers perceived them as adherent. Conclusions: This ACASI-based intervention is easy to use and helps identify nonadherence. The pilot test engendered enhancements including the addition of phone-based adherence counseling. A larger trial is underway to evaluate whether the intervention leads to improved HIV-related outcomes.